Polonyi-Starobinsky supergravity with inflaton in a massive vector multiplet with DBI and FI terms; Classical and Quantum Gravity; Vol. 36, iss. 7 - Abe Hiroyuki; Aldabergenov Ye. Yermek; Aoki Shuntaro; Ketov S. V. Sergey Vladimirovich (2019, 2019)
Title screen